Nanocrystals in drug delivery - Souto, Eliana (Henry Stewart Talks, 2024)
Process in drug discovery techniques, Challenges in formulation development, Pharmaceutical R&D: nanoparticles in industry, Classification of organic nanocarriers, Nanocrystals production approaches, Wet bead milling, Ball milling, Nanocrystals in vivo performance